Investigation of LED Light Qualities for Peppermint (Mentha x Piperita L.) Cultivation Focusing on Plant Quality and Consumer Safety Aspects - Tabbert, Jenny Manuela; Schulz, Hartwig; Krähmer, Andrea (Frontiers in Food Science and Technology, 2022)
To understand how peppermint responds to different LED light qualities during the early vegetative phase, peppermints were illuminated with three different LED light conditions (RB = Red/Blue, RGB = Red/Green/Blue, SUN = artificial sunlight closely resembling the terrestrial sunlight spectrum between 380 and 780 nm) in an automated vertical cultivation system. RB resulted in compact growth, whereas both green-containing lighting conditions induced excessive stem and side branch elongations and significant leaf expansions. Although peppermint plants achieved marketable appearances regardless of lighting condition, essential oil (EO) compositions with highly elevated amounts of pulegone and menthofuran did not meet consumer safety requirements. Both artificial SUN and RB spectra showed lower concentrations of pulegone in the EO at 41 and 43%, respectively, than detected under RGB at more than 49%. Reasons for this undesirable EO composition are discussed as a result of the lighting conditions applied and the early harvest time, leading to an incomplete reduction of pulegone to menthone during biosynthesis. Based on these findings, aromatic peppermint cultivation under LEDs can be improved to meet regulatory requirements and highlights the need for analytical quality controls regarding consumer safety to evaluate the applicability of LED lighting for fresh herb productions.